Integrating Strategic Planning, Distributed Leadership, and Innovation-Driven Technologies for School Improvement - Hamidatul Afifati Fauziah; Nurhana Fakhriyah Imtinan; Hanun Asrohah; Ali Mustofa (STAI Syaichona Moh. Cholil Bangkalan, 2026)
This study aims to analyze the integration of strategic planning, distributed leadership, and innovation-driven technology in improving school quality in the era of digital transformation. The research employs a qualitative approach using a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines. Data were collected from Scopus, Web of Science, ERIC, and Google Scholar databases covering publications from 2015 to 2025. The selection process involved identification, screening, eligibility assessment, and inclusion based on relevance, academic contribution, and alignment with the research focus. The data were analyzed using thematic synthesis to identify patterns, key themes, and conceptual relationships among the selected studies. The findings indicate that sustainable school improvement cannot be achieved through isolated approaches but requires the integration of three core elements: strategic planning as institutional direction, distributed leadership as a collaborative mechanism, and innovation-driven technology as an accelerator of transformation. These elements are mutually reinforcing in enhancing schools’ adaptive capacity to global educational changes. Based on the synthesis, this study proposes “The Nexus of School Improvement” as a conceptual framework that explains the synergistic relationship among the three dimensions. The study contributes theoretically to the development of educational management literature and offers practical implications for policymakers and school leaders in designing sustainable, collaborative, and digitally driven school improvement strategies.